Tafsir Maqâshidi: Definisi, Sejarah Perkembangan Dan Aplikasinya - lufaefi lufaefi; Lukita Fahriana (Ulumuddin)
This article presents various aspects of knowledge about interperpretation of Qur’an, starting from definition, basic principles, epistemology, history of development, and application maqâshidî interpretation to verse of the Qur'an Surah An-Nisâ’[4]:60 about taghut. Analysis to interpret the verse in relation to maqâshidî interpretation is by using analysis maqâshid al-syarîah about the five basic principles in religion, namely maintaining religion (hifz ad-dîn), guard the soul (hifz an-nafs), guard the treasure (hifz al-mâl), guard the honor (hifz al-‘irdh), and guard descendants (hifz nashl). maqâshidî interpretation relevance becomes an analytical tool in understanding the verses of the Qur'an, so that there is a balance between the meaning of the text and the use of context.